2016
DOI: 10.1159/000449358
|View full text |Cite
|
Sign up to set email alerts
|

Remineralizing Potential of a Low Fluoride Toothpaste with Sodium Trimetaphosphate: An in situ Study

Abstract: Objective: To evaluate the effect of a low-fluoride (F) toothpaste supplemented with sodium trimetaphosphate (TMP) on enamel remineralization in situ. Design: Bovine enamel blocks were selected on the basis of their surface hardness (SH) after caries-like lesions had been induced, and randomly divided into 4 treatment groups, according to the toothpastes used: without F or TMP (placebo); 500 ppm F; 500 ppm F plus 1% TMP; and 1,100 ppm F. The study design was blinded and crossover and performed in 4 phases of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
0
22
0
2
Order By: Relevance
“…One way to reduce the potential risk of fluorosis while maintaining the anticaries efficacy of conventional dentifrices is to partly replace fluoride with polyphosphate salts like sodium trimetaphosphate (STMP), calcium glycerophosphate, or hexametaphosphate [da Camara et al, 2016;Takeshita et al, 2016;Zaze et al, 2014]. Among the polyphosphates, STMP is seen to be the most effective anticaries agent with an ability to not only inhibit demineralization, but also to enhance remineralization [Freire et al, 2016;Takeshita et al, 2011].…”
Section: Fluoride Boostersmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to reduce the potential risk of fluorosis while maintaining the anticaries efficacy of conventional dentifrices is to partly replace fluoride with polyphosphate salts like sodium trimetaphosphate (STMP), calcium glycerophosphate, or hexametaphosphate [da Camara et al, 2016;Takeshita et al, 2016;Zaze et al, 2014]. Among the polyphosphates, STMP is seen to be the most effective anticaries agent with an ability to not only inhibit demineralization, but also to enhance remineralization [Freire et al, 2016;Takeshita et al, 2011].…”
Section: Fluoride Boostersmentioning
confidence: 99%
“…The protective barrier against acid diffusion created by the adsorption of STMP on enamel does not seem to hinder the diffusion of Ca 2+ and F -ions into the enamel. In situ models have shown that supplementation of a low-fluoride product with STMP produced similar remineralization effects to a 1,100-ppm fluoride formulation Takeshita et al, 2016], while the addition of STPM to conventional fluoride dentifrices and varnishes significantly enhanced their remineralization of artificial caries lesions Manarelli et al, 2015].…”
Section: Fluoride Boostersmentioning
confidence: 99%
“…Remineralization is believed to occur by the transfer of mineral ions, such as calcium and phosphate, from saliva, plaque fluid, or an external source to the surface of solid-state mineral, therefore promoting ion deposition into crystal voids caused by demineralization ( Elkassas and Arafa, 2014 ). Various modalities of fluoride ( Brighenti et al, 2006 ; Majithia et al, 2016 ), casein phosphopeptides and amorphous calcium phosphate (ACP) ( Poggio et al, 2013 ; Gupta et al, 2016 ), sodium trimetaphosphate ( Takeshita et al, 2016 ), and some natural products ( Zhang et al, 2015 ; Cardoso et al, 2016 ) have been reported to promote remineralization of incipient demineralized lesions. In particular, fluoride dentifrices are widely used for caries prevention and reversal.…”
Section: Introductionmentioning
confidence: 99%
“…One way to reduce the potential risk of fluorosis while maintaining the anticaries efficacy of conventional dentifrices is to partly replace fluoride with polyphosphate salts like STMP, calcium glycerophosphate, or hexametaphosphate [da Camara et al, 2016;Takeshita et al, 2016;Zaze et al, 2014]. Among the polyphosphates, STMP is seen to be the most effective anticaries agent with an ability to not only inhibit demineralization but also enhance remineralization [Freire et al, 2016;Takeshita et al, 2011].…”
Section: Polyphosphates Sodium Trimetaphosphate (Stmp)mentioning
confidence: 99%
“…The protective barrier against acid diffusion created by the adsorption of STMP on enamel does not seem to hinder the diffusion of Ca 2+ and Fions into the enamel. In situ models have shown that supplementation of a lowfluoride product with STMP produced similar remineralization effects to 1100 ppm fluoride formulation [Danelon et al, 2013;Takeshita et al, 2016], while the addition of STPM to conventional fluoride dentifrices and varnishes significantly enhanced their remineralization of artificial caries lesions [Danelon et al, 2015;Manarelli et al, 2015].…”
Section: Polyphosphates Sodium Trimetaphosphate (Stmp)mentioning
confidence: 99%